Modernity, Frontiers and Revolutions
1 online resource (510 pages)
Keywords: The texts presented in Proportion Harmonies and Identities (PHI) - MODERNITY, FRONTIERS AND REVOLUTIONS were compiled with the intent to establish a multidisciplinary platform for the presentation, interaction and dissemination of research. It also aims to foster awareness of and discussion on the topics of Harmony and Proportion with a focus on different visions relevant to Architecture, Arts and Humanities, Design, Engineering, Social and Natural Sciences, and their importance and benefits for the sense of both individual and community identity. The idea of modernity has been a significant driver of development since the Western Early Modern Age. Its theoretical and practical foundations have become the working tools of scientists, philosophers, and artists, who seek strategies and policies to accelerate the development process in different contexts.